2021
DOI: 10.1016/j.heliyon.2021.e07911
|View full text |Cite
|
Sign up to set email alerts
|

Algal amendment improved yield and grain quality of rice with alleviation of the impacts of salt stress and water stress

Abstract: The hazardous effect of abiotic stress and the beneficial effect of organic amendments on rice have been extensively studied during the vegetative stage, but little information is available regarding rice yield. Therefore, the response of rice yield to abiotic stress × organic amendment interaction needs thorough investigation. The differential potency of aqueous extract and biomass of the seaweed Dictyota dichotoma in alleviation of NaCl salinity and PEG-6000 water stress, at Ψ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…BM Extra increases the production of flowering hormones, leading to better early fruit development and fruiting. Other studies have confirmed the effectiveness of applying technology based on the use of algae extracts on barley and rice by improving yield and grain quality [14,15]. A biostimulant containing GA142 improved the percentage and degree of blueberry rooting [16].…”
Section: Effect On Leaf-fruit Ratiomentioning
confidence: 83%
“…BM Extra increases the production of flowering hormones, leading to better early fruit development and fruiting. Other studies have confirmed the effectiveness of applying technology based on the use of algae extracts on barley and rice by improving yield and grain quality [14,15]. A biostimulant containing GA142 improved the percentage and degree of blueberry rooting [16].…”
Section: Effect On Leaf-fruit Ratiomentioning
confidence: 83%
“…This effect was explained by the chemical composition of Undaria biomass, i.e., the presence of plant nutrients such as minerals, vitamins, and phytohormones—cytokinin, gibberellin, and auxin 35 . As shown in the research of El-Katony et al, brown seaweed Dictyota dichotoma used as an organic soil amendment improved the rice ( Oryza sativa ) productivity by enriching the soil with plant macro- and microelements and bioactive compounds (e.g., growth hormones, vitamins, phenolics, flavonoids, fucoidan), increasing the plant resistance to the abiotic stress (salt and water stress) as well as improving the soil structure and capacity to hold the nutrients and water 36 , 37 . Possinger and Amador obtained equivalent or improved yield and quality of sweet corn ( Zea mays ) after adding seaweed dried biomass in two contents: ~ 10,910 kg/dry weight/ha and ~ 21,820 kg dry weight/ha, as compared to preformulated organic fertilizer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…It not only acts as an osmoprotectant to regulate the water balance of plant cells, but also plays important roles in ROS scavenging and stabilizing membranes to prevent electrolyte leakage(Shamsul et al, 2012;Naliwajski et al, 2021). Previous studies reported that the soluble sugar and proline content was evidently enriched when plants are subjected to salt stress, which might contribute to the osmotic and salt stress tolerance of plants(Boriboonkaset et al, 2013;El-Katony et al, 2021), while other studies reported opposite or inconsistent results. For example,Watanabe et al (2000) reported that the total soluble sugar content increased in young Populus euphratica leaves but decreased in the mature leaves after salt stress treatment.…”
mentioning
confidence: 99%